1975
DOI: 10.2135/cropsci1975.0011183x001500040023x
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis of Duration and Rate of Grain Filling of Seven Inbred Lines of Corn1

Abstract: A diallel cross of seven inbred lines of corn (Zea mays L.) was examined for duration of the grain‐filling period, rate of fill, and associated agronomi characters to determine the practicability of selection for these traits. The length of the grain‐filling period and the rate of grain filling differed among hybrids and between years, but interactions between years and hybrids were not detected. Hybrids did not differ for duration of the lag phase of the grain‐filling period.The general combining ability effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
40
0
5

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 0 publications
6
40
0
5
Order By: Relevance
“…This lower genetic contribution on the variation in the filling duration was also reported for indica rice (Li and Senadhira, 1991), although a high genetic effect for the filling duration was obtained for maize (Cross, 1975). The grains on SB had particularly larger environmental and error variance components for this trait, indicating that the environmental conditions and some unknown error factors, which might partly be due to the variation of the heading date in the present materials, influenced more intensively the duration of mling of the grains on SB than of the grains on PB.…”
Section: Discussionsupporting
confidence: 72%
“…This lower genetic contribution on the variation in the filling duration was also reported for indica rice (Li and Senadhira, 1991), although a high genetic effect for the filling duration was obtained for maize (Cross, 1975). The grains on SB had particularly larger environmental and error variance components for this trait, indicating that the environmental conditions and some unknown error factors, which might partly be due to the variation of the heading date in the present materials, influenced more intensively the duration of mling of the grains on SB than of the grains on PB.…”
Section: Discussionsupporting
confidence: 72%
“…These observations support those made earlier by Reddy and Daynard (1983) that maize endosperm cell number, starch granule number, rate of grain fi lling, and kernel mass at maturity are all positively correlated. Cross (1975) observed that maize hybrids with long lag phases tended to have faster rates of grain fi lling. Likewise, Bagnara and Daynard (1982) found positive associations between length of the lag phase, overall rate of endosperm growth, and maximum endosperm dry mass.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these data indicated that increases in total grain yield across decades were combination with a higher rate of grain filling to achieve higher grain yield. Unlike observations made in this study, close associations between grain-filling duration and grain yield have been reported in several studies (Hanway and Russell, 1969;Daynard et al , 1971;Cross, 1975;Fakorede and Mock, 1978;. The relationship between grain yield and rate of grain filling observed in this study corroborates the work of who observed significantly higher rates of grain filling in populations of BSSS(R) and BSCBl(R) which had been improved for grain yield.…”
Section: Discussionsupporting
confidence: 87%
“…The relationship between grain yield and rate of grain filling observed in this study corroborates the work of who observed significantly higher rates of grain filling in populations of BSSS(R) and BSCBl(R) which had been improved for grain yield. Daynard et al (1971) and Cross (1975) found no relationship between rate of grain filling and grain yields.…”
Section: Discussionmentioning
confidence: 95%